Chaotic dynamics of two coaxially-nested cylindrical shells reinforced by two beams; Communications in Nonlinear Science and Numerical Simulation; Vol. 62 - Awrejcewicz J. Jan; Krysko A. V. Anton Vadimovich; Saltykova O. A. Olga Aleksandrovna; Vettsel S. Sergey; Krysko V. A. Vadim (2018, 2018)
Title screen